Innovation policies for advanced biorefinery development: key considerations and lessons from Sweden. (2nd November 2016) - Hellsmark, Hans; Söderholm, Patrik
Abstract: This paper provides an innovation systems perspective on the combination of policy instruments that will be required to stimulate technological development in the advanced biorefinery field. We first consult the established innovation policy literature, and provide a general framework that can be used to identify the type of policy instruments needed to develop new sustainable technology. In a second step, we illustrate how these general principles can be applied in the context of future biorefineries based on either the thermochemical or biochemical conversion of lignocellulosic biomass feedstocks. We draw heavily on the experiences of biorefinery development in Sweden. A central conclusion is that in Sweden, and elsewhere, there are few niche markets for advanced biorefineries and a lack of long‐term policy instruments for the more established renewable fuels. For this reason, there is a need for innovation policy instruments that create markets for renewable fuels and green chemicals, thus supporting technology development during a niche market phase and allowing for the first commercial‐scale plants to be built. The aim of such a policy would be to stimulate learning, form value chains, and experiment with various design options on a larger scale; this complements the use of technology‐neutral policy instruments such as carbon pricing, which primarily promotes the diffusion of mature technologies. The policy instruments that are candidates for the niche market phase include, for example, public procurement and various types of price guarantees. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd